Improving repeated sprint ability by a short period of very high intensity intermittent exercises training in young soccer players - Durand, T.; Dellal, A.; Pialoux, V.; Hautier, C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: The Repeated Sprint Ability (RSA) is often considered as one of the most important skill to develop the physical performance of elite players. However, there is still a lack of study concerning others methods allowing the improvement of the RSA. Therefore, the aim of the present study was to examine the effect of 5-25 and 5-15 intermittent exercises with and without footwork exercises on the RSA performance but also on the maximal speed and an intermittent aerobic test. Methods: Sixteen U19 soccer players (height: 178.0±6.0 m; body mass: 66.6±5.3 kg; body fat: 7.3 ±3.1%) took part in this experimentation. All players performed a 4 week-training period including 5-15-sec and 5-25-sec intermittent exercises with and without footwork exercises. The 5-25-sec and 5-15-sec consisted in 5-sec of work at maximal intensity followed by 25 or 15-sec of passive recovery during 2 blocks of 6 minutes and 4 minutes, respectively. Players performed each intermittent exercise once with specific footwork (consisting in lateral footwork, jumps with ground reaction, skipping, frequency, exercises with hoops) and another time in traditional conditions without specific footwork. Prior and after this 4 week-training period, each player performed a RSA Test (10 x 30-m interspaced by 30-sec of active recovery), an intermittent fitness test (30-15 IFT) and a 10-m and 30-m sprint performance test. Heart rate (HR) and rating of perceived exertion (RPE) were monitored during and after each test and intermittent exercises training. Results: The 4-week training period of very high-intensity intermittent exercise induced a significant increase of the 30-15 IFT and RSA performances (p<0.05), whereas the 10-m and 30-m sprint performance was unchanged. Complementary, the 5-25 intermittent exercise without footwork exercises allows to reach similar HR and RPE values than during RSA. On the contrary, for the intermittent exercises with footwork exercise, the HR and RPE are less important than during the tests. Discussion: According to these results, it appears that the short intermittent exercises at very high-intensity (combination of 5-25-sec and 5-15-sec) seems to be appropriate for the development of both the repetition of high intensity actions (RSA) and intermittent fitness performance (30-15 IFT). It should be suggested to alternate between very high-intensity intermittent exercises and RSA training in order to develop the physical performance in youth players. Furthermore, it could be interesting that future study will examine if a period of smallsided games training induce similar effects than RSA or short duration of intermittent exercises.